Retrospective cohort study on alkaline phosphatase and ICU mortality rate of multiple myeloma - Qian-hui Wang; Gui-xin Dong; Hai-bo Cong (Scientific Reports, 2025)
Abstract Alkaline phosphatase has a different clinical significance in multiple myeloma than in other neoplasms. Changes in alkaline phosphatase levels may serve as a good predictor in patients with multiple myeloma in the intensive care unit. However, evidence on the relationship between alkaline phosphatase and mortality in patients with multiple myeloma in the ICU is lacking. A retrospective cohort study was conducted involving 161 participants retrieved from the Medical Information Mart for Intensive Care database. The exposure factor was alkaline phosphatase, and the outcome variable was ICU mortality. We assessed the relationship between alkaline phosphatase levels and ICU in-hospital mortality by curve fitting and multivariate adjusted Cox regression analysis and inflection point analysis. A total of 161 subjects were enrolled, including 101 males (62.7%) and 60 females (37.3%), and curve fitting analysis showed a nonlinear relationship between alkaline phosphatase level and ICU mortality risk (nonlinear P = 0.021). When using alkaline phosphatase levels of 100–659 IU/L as reference, 22–62 IU/L alkaline phosphatase (compared to 63–99 IU/L) was associated with lower mortality, with the lowest risk being 50.682 IU/L. Our data analysis suggests that alkaline phosphatase has a nonlinear relationship with ICU in-hospital mortality in patients with multiple myeloma. When the alkaline phosphatase level was about 50.682 IU/L, the ICU in-hospital mortality rate was the lowest, which had certain clinical significance and deserved further study.